2005
DOI: 10.1002/14651858.cd002011.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Conventional chest physiotherapy compared to other airway clearance techniques for cystic fibrosis

Abstract: Conventional chest physiotherapy compared to other airway clearance techniques for cystic fibrosis. Cochrane Database of Systematic Reviews, (1), [ARTN CD002011.pub2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 49 publications
3
81
1
13
Order By: Relevance
“…Intervention studies were excluded due to the effect of participating in a formal research trial, in which greater monitoring/measurement of patients would take place. Indeed, compared with a previous review of randomized controlled trials examining adherence rates for airway clearance techniques (88 -96%), 14 rates for compliance in observational studies reported in the present study are lower (33.3-91.2%). The previous review of adherence to antibiotics (mixed methodologies) reported similar adherence rates (35-87%) 13 compared with the present review (36 -85%).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Intervention studies were excluded due to the effect of participating in a formal research trial, in which greater monitoring/measurement of patients would take place. Indeed, compared with a previous review of randomized controlled trials examining adherence rates for airway clearance techniques (88 -96%), 14 rates for compliance in observational studies reported in the present study are lower (33.3-91.2%). The previous review of adherence to antibiotics (mixed methodologies) reported similar adherence rates (35-87%) 13 compared with the present review (36 -85%).…”
Section: Discussioncontrasting
confidence: 85%
“…Adherence rates have been reported to be 67% for oral antibiotics, 31-53% for inhaled antibiotics, 7 33% for dornase alfa, and 40 -70% for chest physical therapy. 3,[8][9][10][11][12] Although adherence levels for subcategories of 2 of the 4 WHO recommendations have been the subject of systematic reviews (adherence to antibiotics only, 13 airway clearance techniques 14 ), the inclusion of randomized controlled trials may not reflect participants' level of adherence to their independent home treatment regimes due to the nature of frequent monitoring as part of being involved in a trial. Hence, this review was undertaken to include all 4 WHO recommendations (nutrition, medication, exercise, pancreatic enzyme replacement therapy) in non-interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…51 This evaluation is performed systematically and rigorously, the results of which are based on the strength of the evidence found in the literature. Systematic ACT reviews are available and include reviews of specific techniques, such as active cycle of breathing, 52 positive expiratory pressure devices, 53 and oscillatory positive expiratory pressure devices, 54 as well as sequencing pharmacologic agents, 55,56 and comparing therapeutic modalities for specific diseases such as CF 57 or COPD. 58…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Evaluation of the need for ACT and use of a particular device or technique must include initial and ongoing assessment of the patient's lung function, muscle strength, and cognitive ability to perform the therapy. Figure 3 integrates expert opinion, 12,17 evidence from published systematic reviews, [52][53][54]57,58 and clinical practice guidelines 59,60 to construct an algorithm to guide the use of ACT. The establishment and evaluation of patient, process, and financial outcomes are crucial elements in protocol implementation.…”
Section: Putting Evidence Into Practicementioning
confidence: 99%
“…The range of techniques has recently been evaluated in six Cochrane reviews ( Van der Schans, et al, 2000;Elkins et al, 2004;Main et al, 2005;Moran et al, 2009;Morrison & Agnew, 2009;Robinson et al, 2010). The conclusions from these Cochrane reviews are that: -1.…”
Section: Do Airway Clearance Techniques Work In Reality? (Cochrane Rementioning
confidence: 99%